The Effect of the Foot Reflection Therapy toward Systolic Blood Pressure in Patients with Primary Hypertension - Liota Marsha Renardiyarto; Dwi Ari Murti Widigdo; Tulus Puji Hastuti (Universitas Padjadjaran, 2018)
Hypertension is a high blood pressure disorder which disrupts blood flow resulting in blocking of oxygen and nutrition carried by the blood to body tissue. Based on Dinas Kesehatan Jawa Tengah's data, hypertension became one of the health issues with a percentage of 37%. One of non-pharmacological therapy is foot-reflexology therapy. This method gives a relaxation effect that could make blood circulating better, decay the blocking in blood vessel, nourish muscles and nerves, and strenghten heart activity. Objective: To determine the effect of foot reflection therapy toward systolic blood pressure in primary hypertension patient at Ngadirojo, Secang, Magelang Method: This study used the pre-experiment method with one group pre-test post-test design without a control group. Simple random sampling technic was used to get 46 subjects. Result: Wilcoxon Test result showed different significant in this study between pre-post test foot reflection therapy by p=0.000 (p<0.05). It meant there was an effect of foot-reflection therapy on systolic blood pressure in primary hypertension. The average of blood pressure decrease was 3,7 mmHg. Although, the results of this study showed that there was a significantly different decrease in this decrease was not clinically significant. The recommendation is made to conduct a study in a combination of pharmacology and non-pharmacology intervention to lower blood pressure.